Keanekaragaman Bivalvia Di Pantai Teluk Bogam Kec. Kumai Kab. Kotawaringin Barat Kalimantan Tengah - Ridha Nirmalasari (Universitas Hasanuddin, 2019)
Research on diversity of bivalvia in Teluk Bogam Beach, Kumai subdistrict, Kotawaringin Barat regencyt, Central Kalimantan. This research aims to know diversity of bivalvia species that live on sandy substrates and muddy substrates. This research was conducted in July-September 2018. Sampling used purposive sampling technique, then identified and calculated diversity index, evenness, density, relative density and dominance. Based on the results of the study, 6 species found were Anadara granosa, Meretrik meretrik, Perna viridis, Placenta Placuna, Hiatula chinensis, Semele cordiformis. The level of diversity on sandy substrate is 1.5764 while the muddy substrate is 1.1269 including the criteria for the low diversity index. Evenness value on sandy substrate is 2.0238 and muddy substrate is 1.434 when seen from the evenness criteria both have very high evenness value. The density index on the overall sandy substrate is 26.8 ind/m2 and the overall muddy substrate is 16.3 ind/m2, the index of relative density on the sandy substrate is 61.594% and the relative density of the muddy substrate is 38.03%. Dominance index on sandy substrate was 1.7253 while on muddy substrate was 9,944. The physical chemical quality of water based on observations of water temperature ranged from 270C - 300C, DO ranged from 6.2 mg/l – 7.41 mg/l and pH 7.00.